TEMPAT PEMBUANGAN AKHIR (TPA) KALIORI SEBAGAI WISATA EDUKASI DI KABUPATEN BANYUMAS DENGAN PENEKANAN DESAIN PADA PENGOLAHAN SEKUEN RUANG - Santoso, Astya Jayanti Kurnia; Purnomo, MDE; Sumaryoto, Sumaryoto (Universitas Sebelas Maret Surakarta, 2016)
Tempat Pembuangan Akhir (TPA) Kaliori is one of landfills in Banyumas whose sanitary landfill system which is a well-planned waste management system. TPA Kaliori is one of the government's efforts in improving the waste management system in Indonesia. TPA Kaliori is initiated into educational tourism destination by Banyumas regent period 2013 – 2018. Educational tourism in TPA Kaliori is expected to be a means of education about waste. To be presented communicatively based on order/sequence is the key to well-delivered information. The issue is how to design waste management facilities as well as educational tourism with the sequence based in waste treatment process. The objective of this scheme is to get the design of TPA Kaliori as a facility for waste processing and educational tourism activities with an emphasis on designing sequence of spaces. The method used is a method of architectural design with an emphasis on the sequence of spaces. The results obtained, is the design of TPA Kaliori as waste treatment facilities and educational tourism with an emphasis on designing sequence of spaces. The spaces are connected by a circulation that will automatically guide the user to follow a sequence. Keywords: educational tourism, landfill, sequence of space, TPA Kaliori, waste management